Conductance Change Induced by the Rashba Effect in the LaAlO3/SrTiO3 Interface - Kim, Taeyueb; Kim, Shin-Ik; Baek, Seung-Hyub; Hong, Jinki; Koo, Hyun Cheol (AMER SCIENTIFIC PUBLISHERS, 2015)
The LaAlO3/SrTiO3 (LAO/STO) heterostructure has an inherent space inversion asymmetry causing an internal electric field near the interface. The Rashba spin-orbit coupling arising from this structural characteristic has a considerable influence on spin transport. With application of an external magnetic field, we observed conductance change in the LAO/STO interface which depends on the sign and magnitude of the field. Our systematic study revealed that these results come from spin dependent transport, by which we obtained quantitative strength of the Rashba effect. The Rashba strength in this system depends on the temperature: it varies from 2.6 x 10(-12) eVm to negligible value in the temperature range of 1.8 K similar to 12 K. This method for detecting Rashba effect covers a wider temperature range in comparison with those obtained from Shubnikov-de Haas oscillation or weak antilocalization measurements.
Keywords: ELECTRON-GAS; SPIN